The occurrence of microbial hazards and succession of Enterobacteriaceae on fresh - cut fruit during minimal processing and storage - Buys, E.M. (Elna Maria) (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 2014.